Kiss my math : showing pre-algebra who's boss - McKellar, Danica (New York : Plume, 2009)
Presents a pre-algebra primer for seventh- to ninth-graders, in a reference that shares time-saving tricks, real-world examples, and detailed practice problems
Includes index
Keywords: Algebra -- Study and teaching; Algebra -- Problems, exercises, etc; Algebra -- Study and teaching (Secondary) -- United States; Mathematics -- Study and teaching (Secondary) -- United States; Girls -- Education -- United States; Girls -- United States -- Psychology